2010
DOI: 10.1021/nl100415q
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Förster Resonance Energy Transfer in Solid-State Dye Sensitized Solar Cells

Abstract: Solid-state dye-sensitized solar cells (SS-DSCs) offer the potential to make low cost solar power a reality, however their photoconversion efficiency must first be increased. The dyes used are commonly narrow band with high absorption coefficients, while conventional photovoltaic operation requires proper band edge alignment significantly limiting the dyes and charge transporting materials that can be used in combination. We demonstrate a significant enhancement in the light harvesting and photocurrent generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 49 publications
(78 reference statements)
3
77
0
Order By: Relevance
“…The concept of ET from sensitizers such as colloidal semiconductor quantum dots [22][23][24] , dye molecules [25][26][27][28] or silicon NCs 29-31 is widely used. It can, for example, improve the spectral response of photovoltaic devices, increase the output of phosphors or optical amplifiers or be used for colour tuning in lighting.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ET from sensitizers such as colloidal semiconductor quantum dots [22][23][24] , dye molecules [25][26][27][28] or silicon NCs 29-31 is widely used. It can, for example, improve the spectral response of photovoltaic devices, increase the output of phosphors or optical amplifiers or be used for colour tuning in lighting.…”
Section: Discussionmentioning
confidence: 99%
“…A similar sensitization concept has only recently proven to be benefi cial for dye sensitized and hybrid solar cells. [23][24][25][26][27] For OPV devices theoretical and experimental sensitization studies have been reported using special dyes and acceptor molecules. [28][29][30][31][32] Charge and energy transfer mechanisms involving fullerenes have been discussed in the past and remain a hotly debated topic.…”
Section: Perylene Sensitization Of Fullerenes For Improved Performancmentioning
confidence: 99%
“…[5] But it is also widely used when considering EET between semiconducting nanocrystals and molecules attached to their surface as well as among different nanocrystals. [6,7] Potential application in photovoltaics [8][9][10] has focused current research interests on EET in specifically arranged supramolecular complexes which should act as artificial light-harvesting antennae.…”
Section: Introductionmentioning
confidence: 99%